1992
DOI: 10.1002/jcp.1041510220
|View full text |Cite
|
Sign up to set email alerts
|

Variations in tumor cell growth rates and metabolism with oxygen concentration, glucose concentration, and extracellular pH

Abstract: Tumors and multicellular tumor spheroids can develop gradients in oxygen concentration, glucose concentration, and extracellular pH as they grow. In order to calculate these gradients and assess their impact on tumor growth, it is necessary to quantify the effect of these variables on tumor cell metabolism and growth. In this work, the oxygen consumption rates, glucose consumption rates, and growth rates of EMT6/Ro mouse mammary tumor cells were measured at a variety of oxygen concentrations, glucose concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
280
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(295 citation statements)
references
References 22 publications
14
280
0
1
Order By: Relevance
“…However, the up-regulation was not sufficiently large to compensate for the loss in energy generation resulting from the inhibition of the oxidative pathway. The effects of hypoxia on glycolysis and adenylate energy charge reported here for human melanoma cells are thus consistent with those reported previously for rodent tumour cells and other histological types of human tumour cells (Rotin et al, 1986;Heacock and Sutherland, 1990;Casciari et al, 1992;Gerweck et al, 1992).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the up-regulation was not sufficiently large to compensate for the loss in energy generation resulting from the inhibition of the oxidative pathway. The effects of hypoxia on glycolysis and adenylate energy charge reported here for human melanoma cells are thus consistent with those reported previously for rodent tumour cells and other histological types of human tumour cells (Rotin et al, 1986;Heacock and Sutherland, 1990;Casciari et al, 1992;Gerweck et al, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…Experimental studies have suggested that the energy status is particularly low in hypoxic tumour cells at PHe in the lower part of this range, because of inhibited glycolysis owing to the low PHe (Halperin et al, 1969;Rotin et al, 1986;Casciari et al, 1992;Gerweck et al, 1993). However, the adenylate energy charge at pHe 6.6 was similar to that at pHe 7.4 and 7.0 in hypoxic cultures of the cell lines studied here, even though the rate of glucose uptake was lower at PHe 6.6, than at PHe 7.4 and 7.0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth characteristics and the metabolism of the EMT6/Ro spheroid (mouse mammary carcinoma cells) have been extensively investigated (Mueller-Klieser and Sutherland, 1982, Mueller-Klieser, 1984, Freyer and Sutherland, 1985, Freyer and Sutherland, 1986a, Casciari et al, 1988, Freyer, 1988, Walenta et al, 1990, Freyer et al, 1991, Casciari et al, 1992, Casciari et al, 1992a. In Freyer and Sutherland (1986a) in particular, the radius of the necrotic core for spheroids of different size and under different oxygen and glucose concentrations in the medium were reported.…”
Section: Necrotic Core In Emt6/ro Spheroidsmentioning
confidence: 99%